2002
DOI: 10.1111/j.1748-5827.2002.tb00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a high fibre diet on glycaemic control and quality of life in dogs with diabetes mellitus

Abstract: A study was undertaken to evaluate a high fibre diet used in the management of 10 dogs with naturally occurring insulin-dependent diabetes mellitus. Following baseline measurements of health and glycaemic control, the dogs were fed a canned diet containing a blend of insoluble and soluble dietary fibres and were monitored during the ensuing four months. Switching to the high fibre diet was associated with significantly lower mean 24-hour and postprandial plasma glucose concentrations, which were maintained ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 9 publications
1
33
1
3
Order By: Relevance
“…Differences can depend on the illness (Varni and others 2006, Wilson‐Genderson and others 2007) and the facets considered (Eiser and Morse 2001, Hexdall and Huebner 2007). One veterinary research paper incidentally reported some differences between proxies in assessing demeanour (Graham and others 2002). Such discrepancies may represent significant concerns about the validity of either group of responses, or it may be that disagreements are over‐represented in literature.…”
Section: What To Assess?mentioning
confidence: 99%
See 1 more Smart Citation
“…Differences can depend on the illness (Varni and others 2006, Wilson‐Genderson and others 2007) and the facets considered (Eiser and Morse 2001, Hexdall and Huebner 2007). One veterinary research paper incidentally reported some differences between proxies in assessing demeanour (Graham and others 2002). Such discrepancies may represent significant concerns about the validity of either group of responses, or it may be that disagreements are over‐represented in literature.…”
Section: What To Assess?mentioning
confidence: 99%
“…Some veterinary studies have usefully assessed particular facets of QOL. Graham and others (2002) assessed QOL by the use of two parameters, demeanour and activity. Their study considered diabetes mellitus, for which these are especially relevant facets.…”
Section: What To Assess?mentioning
confidence: 99%
“…, 1995). Carbohydrate metabolism has been demonstrated to be influenced by dietary fibre, and high fibre diets are of benefit in the management of diabetic dogs (Graham et al. , 2002).…”
Section: Dietary Weight Reduction Programmesmentioning
confidence: 99%
“…Evaluating beet pulp, guar gum and inulin incorporated in the basal diet of healthy dogs, DIEZ et al (1998) did not find any changes on glucose meal response ------------------------------------------------------------- with the supplementation of the fibres in study, and only a reduction on plasma insulin was verified after guar gum dietary addition. Fibres, however, may have effect when supplemented to dogs with diabetes mellitus, in such particular health situation high fibre diets may reduce glucose concentration after the meal, helping the insulin administration in the control of glucose blood concentration (GRAHAM, et al, 2002). In addition, very high soluble fibre inclusion can change glucose meal response of health dogs, as demonstrated after the supplementation of 15 to 20% of guar gum (on DM basis) (BLAXTER et al, 1990).…”
Section: Discussionmentioning
confidence: 99%